COVID-19 Orthopaedic Safe Care Toolset: Guidelines for the Diagnosis and Management of Patients with Fracture and COVID-19. (1st July 2020) - Mi, Bobin; Xiong, Yuan; Lin, Ze; Panayi, Adriana C.; Chen, Lang; Liu, Guohui
Abstract : Abstract: The SARS-CoV-2 (severe acute respiratory syndrome-coronavirus 2) was reported in Wuhan, Hubei Province, People's Republic of China, and, subsequently, in other provinces and regions across the People's Republic of China and >212 countries. COVID-19, the disease caused by this coronavirus, was declared a worldwide pandemic by the World Health Organization (WHO). The incidence of patients with fracture who are also positive for COVID-19 is on the rise. The diagnosis and management of such patients can be complicated as their clinical characteristics are heterogeneous. Furthermore, a surgical procedure can be particularly challenging given that the use of high-speed devices results in aerosol generation. In this study, we develop and propose globally applicable guidelines to fill this knowledge gap and we identify and propose the necessary protective strategies for medical personnel in an orthopaedic emergency department and in the inpatient wards. We also introduce diagnostic criteria, surgical complication management, and follow-up strategies for infected patients. These guidelines may be helpful to decrease the infection rate of orthopaedic trauma personnel and to provide diagnosis and treatment therapy for patients with fracture and COVID-19.